MATHEMATICAL MODELING OF RESOURCES-ECONOMY PROCESS OF CONTINUOUS CASTING IN STRIP CRYSTALLIZERS - E. I. Marukovich; V. A. Pumpur; V. M. Iljushenko; Ju. V. Petrunja (Литьë и металлургия, 2007)
The mathematical model of casting process and numerical investigations on determination of the continuous casting fitting parameters for production of slugs of zinc anodes are described.